Implementasi Diplomasi Pendidikan dan Diplomasi Budaya melalui Program Indonesian International Student Mobility Awards (IISMA) - Caroline Kristiana; Ronaldo Benito (Indonesian Perspective, 2023)
Amidst the rapid influx of technology, the Indonesian government must prepare for the future evolution of culture and job skills. One of the realizations of this preparation is through the implementation of the Merdeka Belajar — Kampus Merdeka (MBKM) policy. This research discusses how educational diplomacy and cultural diplomacy are implemented through the Indonesian International Student Mobility Awards (IISMA), one of the flagship programs of MBKM. Using a descriptive qualitative method based on literature review, in-depth interviews, and observation, the authors describe this phenomenon through the concepts of soft power and public diplomacy. The results of this research indicate that the implementation of IISMA aims to build nation branding and a positive image of Indonesia in the eyes of the world, as well as to accelerate the improvement of education quality in Indonesia and promote cultural diversity. This program is a correct step towards achieving peaceful foreign policy goals and prioritizing human resource investment, although overall results require a long-term process.